2023
DOI: 10.1021/acsnano.3c01836
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Multispectral Mechano-Optical System for Multipurpose Applications

Abstract: Mechano-optical systems with on-demand adaptability and a broad spectrum from the visible to microwave are critical for complex multiband electromagnetic (EM) applications. Most existing material systems merely have dynamic optical or microwave tunability because their EM wave response is strongly wavelength-dependent. Inspired by cephalopod skin, we develop an adaptive multispectral mechano-optical system based on bilayer acrylic dielectric elastomer (ADE)/silver nanowire (AgNW) films, which reconfigures the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(32 citation statements)
references
References 52 publications
(117 reference statements)
0
32
0
Order By: Relevance
“…According to eq , the dielectric loss mechanism mainly encompasses polarization loss ( ε p ) and resistance loss ( ε σ ). The resistance loss is proportional to the conductivity, which in turn is related to the graphitization degree of the MPN-derived PC layer. , From the Raman spectra results, it can be seen that the graphitization degree and resistance loss increase significantly as the pyrolysis temperature increases from 600 to 700 °C/800 °C. The PC in the PC/ZnO-700 and -800 composites can act as a conductive network in the paraffin matrix and promote electron movement, which would result in the generation of microcurrents and consequent electromagnetic wave energy dissipation. , According to the Debye relaxation theory, when the resistance loss is negligible, ε′ and ε″ obey the following equation: true( ε ε s + ε 2 true) 2 + ε 2 = true( ε s ε 2 true) 2 If the ε′−ε″ curve has the form of a semicircle, it can be concluded that the tested material dissipates energy via a polarization relaxation process, and each semicircle corresponds to an individual Debye relaxation process .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…According to eq , the dielectric loss mechanism mainly encompasses polarization loss ( ε p ) and resistance loss ( ε σ ). The resistance loss is proportional to the conductivity, which in turn is related to the graphitization degree of the MPN-derived PC layer. , From the Raman spectra results, it can be seen that the graphitization degree and resistance loss increase significantly as the pyrolysis temperature increases from 600 to 700 °C/800 °C. The PC in the PC/ZnO-700 and -800 composites can act as a conductive network in the paraffin matrix and promote electron movement, which would result in the generation of microcurrents and consequent electromagnetic wave energy dissipation. , According to the Debye relaxation theory, when the resistance loss is negligible, ε′ and ε″ obey the following equation: true( ε ε s + ε 2 true) 2 + ε 2 = true( ε s ε 2 true) 2 If the ε′−ε″ curve has the form of a semicircle, it can be concluded that the tested material dissipates energy via a polarization relaxation process, and each semicircle corresponds to an individual Debye relaxation process .…”
Section: Resultsmentioning
confidence: 98%
“…The resistance loss is proportional to the conductivity, which in turn is related to the graphitization degree of the MPN-derived PC layer. 54,55 From the Raman spectra results, it can be seen that the graphitization degree and resistance loss increase significantly as the pyrolysis temperature increases from 600 to 700 °C/800 °C. The PC in the PC/ZnO-700 and -800 composites can act as a conductive network in the paraffin matrix and promote electron movement, which would result in the generation of microcurrents and consequent electromagnetic wave energy dissipation.…”
Section: Resultsmentioning
confidence: 99%
“…The reflection loss of different composite ratios of BaFe 12 O 19 @PVDF composite materials can be determined using formulas and , normalR normalL = 20 lg | Z Z 0 Z + Z 0 | goodbreak0em2em⁣ ( Z 0 = μ 0 ε 0 , Z = Z 0 μ ε ) Z = Z 0 tanh ( i 2 π f d c μ ε ) …”
Section: Resultsmentioning
confidence: 99%
“…Reflection Loss. The reflection loss of different composite ratios of BaFe 12 O 19 @PVDF composite materials can be determined using formulas 1 and 2 38,39 i k j j j j j y According to eqs 1 and 2, the 2D reflection loss curve of BaFe 12 O 19 @PVDF can be calculated. Figure 11 shows the 2D absorption reflection loss of pure-phase BaFe 12 O 19 and BaFe 12 O 19 @PVDF composites with different mass ratios.…”
Section: Hexagonal Flakementioning
confidence: 99%
“…What is more, with the antagonized development of radar detection technology and radar stealth technology, the radar working frequency band is gradually concentrated in the low-frequency region. It is imminent to research the radar stealth technology in low frequencies. Consequently, the development of microwave absorption (MA) materials in the low-frequency band has assumed critical importance. Carbon-based materials are highly sought after as microwave absorbers due to their excellent dielectric loss ability, lightweight, and easy accessibility, which more than meet the requirements of modern MA materials.…”
Section: Introductionmentioning
confidence: 99%